Pulmonary Delivery of Curcumin and Beclomethasone Dipropionate in a Multicomponent Nanosuspension for the Treatment of Bronchial Asthma - Luca Casula; Francesco Lai; Elena Pini; Donatella Valenti; Chiara Sinico; Maria Cristina Cardia; Salvatore Marceddu; Giorgia Ailuno; Anna Maria Fadda (MDPI AG, 2021)
Curcumin has shown a potential extraordinary activity as an add-on ingredient in asthma treatment, due to its immunomodulatory and anti-inflammatory mechanism of action. However, its low water solubility and bioavailability lead to a poor therapeutic effect, which can be overcome by its formulation as nanocrystals. The aim of this study was to prepare a multicomponent formulation for the delivery of curcumin (CUR) and beclomethasone dipropionate (BDP) into the lungs as water-based nanosuspensions (NS). Single component formulations (CUR-NS, BDP-NS) and a multicomponent formulation (CUR+BDP-NS) were prepared through a wet ball media milling technique, using P188 as a non-toxic stabilizer. Characterization was carried out in terms of size, size distribution, zeta potential, nanocrystals morphology, and solid-state properties. Moreover, the inhalation delivery efficiency was studied with Next Generation Impactor (NGI, Apparatus E Ph. Eu). CUR-NS was optimized and showed a long-term stability and improved nanocrystals apparent solubility. The three formulations exhibited a nanocrystal mean diameter in the range of 200-240 nm and a homogenous particle size distribution. Aggregation or sedimentation phenomena were not observed in the multicomponent formulation on 90 days storage at room temperature. Finally, the nebulization tests of the three samples showed optimal aerodynamic parameters and MMAD < 5 µm.